Against wellbeing: The problem of resources, metrics and care of the self. (June 2021) - Murphy, Brendon
This article critically engages with the concept and practice of 'wellbeing'. Over the last decade, managerial practices have broadly introduced 'wellbeing' policies into the workplace, including the legal workplace. While these practices, in principle, can offer important forms of support for staff under professional stress, they can also be counterproductive, and have the effect of escalating stress and isolation. Drawing on Foucault, this article turns wellbeing on its head and identifies the dark side of what has become a widely practised form of control. It concludes by advocating for employee dialogue and genuine care rather than responsibilising employees for systemic failings.